PENYAJIAN JURNALISTIK ONLINE INFOBDG UNTUK MENJADI SUMBER INFORMASI KREDIBEL - Dewi Rani; Sri Dewi Setiawati (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2020)
This research deals with Infobdg online journalism through social media. The purpose of this study is to analyze Infobdg's efforts to become a credible source of information. The method used is a qualitative method with data collection techniques through interviews. The results of this study indicate that Infobdg efforts to become a credible source of information are good enough by fulfilling the credibility element seen from the elements of trustworthiness, accuracy, bias, completeness of the news (completeness). Infobdg consistently prioritizes truth rather than speed in providing information to the public.